Results from Viet Nam's 2022 report card on physical activity for children and youth - Phuong Nguyen; Dan Xuan Nguyen; Long Khanh-Dao Le; Jaithri Ananthapavan; Phan Danh Na; Hong K. Tang (Elsevier, 2023)
Background/Objective: The Active Healthy Kids 2022 Viet Nam Report Card provides an evidence-based assessment of 10 indicators of community and government-led initiatives that impact the physical activity levels of children and youth in Vietnam. Methods: A systematic framework developed by the Active Healthy Kids Global Alliance was used. Each indicator: Overall Physical Activity, Organized Sport Participation, Active Play, Active Transportation, Sedentary Behaviors, Physical Fitness, Family and Peers, School, Community and Environment, and Government, and a new indicator: Obesity was assessed against predefined benchmarks. EBSCOhost databases and Google Scholar were searched for relevant academic and grey literature (e.g., government reports) respectively to inform indicator grading. Results: The School indicator received the highest grade 'A', followed by the Government indicator which was graded as 'B-'. Three indicators (Sedentary Behaviors, Family and Peers, Community and Environment) received 'C' grades. Active Transportation was graded 'D+'. Overall Physical Activity received the lowest grade of 'F'. Organized Sport and Physical Activity, Active Play, and Physical Fitness were not graded due to lack of data. Obesity was graded B-. Conclusions: This is the first physical activity report card for children and adolescents in Viet Nam. Evidence suggests that Vietnamese children and adolescents have low physical activity levels and high levels of sedentary behaviors. Initiatives to promote physical activity in children predominantly focus on promoting physical education in schools. Increased community-based programs promoting physical activity outside of school settings are required. Future research should address the surveillance gap in Organized Sport and Physical Activity, Active Play, and Physical Fitness.